The oxidized phospholipid POVPC impairs endothelial function and vasodilation via uncoupling endothelial nitric oxide synthase. (November 2017) - Yan, Feng-Xia; Li, Hua-Ming; Li, Shang-Xuan; He, Shi-Hui; Dai, Wei-Ping; Li, Yan; Wang, Tian-Tian; Shi, Mao-Mao; Yuan, Hao-Xiang; Xu, Zhe; Zhou, Jia-Guo; Ning, Da-Sheng; et al.
Abstract: Endothelial dysfunction is an early stage of atherosclerosis. We recently have shown that 25-hydroxycholesterol found in atherosclerotic lesions could impair endothelial function and vasodilation by uncoupling and inhibiting endothelial nitric oxide synthase (eNOS). 1-Palmitoyl-2-(5-oxovaleroyl)-sn-glycero-3-phosphocholine (POVPC), the oxidation product of oxidized low-density lipoprotein, is another proinflammatory lipid and has also been found in atherosclerotic lesions. However, whether POVPC promotes atherosclerosis like 25-hydroxycholesterol remains unclear. The purpose of this study was to explore the effects of POVPC on endothelial function and vasodilation. Human umbilical vein endothelial cells (HUVECs) were incubated with POVPC. Endothelial cell proliferation, migration and tube formation were measured. Nitric oxide (NO) production and superoxide anion generation (O 2 − ) were determined. The expression and phosphorylation of endothelial nitric oxide synthase (eNOS), AKT, PKC-βII and P70S6K as well as the association of eNOS and heat shock protein 90 (HSP90) were detected by immunoblotting and immunoprecipitation. Endothelial cell apoptosis was monitored by TUNEL staining. The expression of Bcl-2, Bax, and Cleaved Caspase 3 were detected by immunoblotting. Finally, aortic ring from C57BL6 mice were isolated and treated with POVPC and the endothelium-dependent vasodilation was evaluated. POVPC significantly inhibited HUVECs proliferation, migration, tube formation, decreased NO production but increased O 2 − generation. POVPC inhibited the phosphorylation of Akt and eNOS at Ser1177, increased activation of PKC-βII, P70S6K and the phosphorylation of eNOS at Thr495, reduced the association of HSP90 with eNOS. Meanwhile, POVPC induced endothelial cell apoptosis by inhibiting Bcl-2 expression, increasing Bax and cleaved caspase-3 expressions as well as caspase-3 activity and impaired endothelium-dependent vasodilation. These data demonstrated that POVPC impaired endothelial function by uncoupling and inhibiting eNOS as well as by inducing endothelial cell apoptosis. Therefore, POVPC may play an important role in the development of atherosclerosis and may be considered as a potential therapeutic target for atherosclerosis. Highlights: POVPC impaired endothelial function by uncoupling and inhibiting eNOS and endothelial cell apoptosis. POVPC may play an important role in the development of atherosclerosis. POVPC may be considered as a potential therapeutic target for atherosclerosis.